Strength and Chemical Characterization of Ultra High-Performance Geopolymer Concrete: A Coherent Evaluation - Midhin A. K. Midhin; Leong Sing Wong; Ali Najah Ahmed; Al Mashhadani D. A. Jasim; Suvash C. Paul (Civil Engineering Journal, 2023)
The objective of this review article is to analyze published data encompassing compressive strength, tensile strength, elastic modulus, and flexural strength, as well as the utilization of scanning electron microscopy (SEM), energy dispersive x-ray spectroscopy (EDS), and x-ray diffraction (XRD) for Ultra High-Performance Geopolymer Concrete (UHP-GC), with the focus of establishing the current research trends regarding its mechanical, microstructural, and chemical characteristics. After a critical evaluation of the published data from the literature findings, it became evident that UHP-GC can attain a remarkably high level of engineering performance. In UHP-GC, the optimum percentage of silica fume as a slag partial replacement to achieve high compression, tensile, and elastic modulus were traced to be 25, 30, and 35%, respectively. The optimum ratio of sodium silicate to sodium hydroxide and sodium hydroxide molarity for UHP-GC were identified to be 3.5 and 16, respectively. All in all, the review provides a thorough understanding of the review gap and distinct functions of different raw materials in decreasing porosity and enhancing the formation of geopolymeric gels that not only bond but also strengthen UHP-GC. UHP-GC stands as an energy-saving material in concrete technology, poised to forge a path towards a sustainable future for the building sector. Doi: 10.28991/CEJ-2023-09-12-020 Full Text: PDF